2017
DOI: 10.3389/fpsyg.2016.02081
|View full text |Cite
|
Sign up to set email alerts
|

Convergence in the Bilingual Lexicon: A Pre-registered Replication of Previous Studies

Abstract: Naming patterns of bilinguals have been found to converge and form a new intermediate language system from elements of both the bilinguals’ languages. This converged naming pattern differs from the monolingual naming patterns of both a bilingual’s languages. We conducted a pre-registered replication study of experiments addressing the question whether there is a convergence between a bilingual’s both lexicons. The replication used an enlarged set of stimuli of common household containers, providing generalizab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
(115 reference statements)
1
7
0
Order By: Relevance
“…This idea has previously been proposed in the literature (for review, see Abutalebi, 2008) based on Green's convergence hypothesis (Green, 2003), which claims that language representations should converge and the neural differences should disappear as proficiency increases. Indeed, our results are coherent with this hypothesis and confirm that L2 proficiency has a major impact on the neural resources needed to manipulate two languages, in accordance with other studies (e.g., Consonni, Cafiero, Marin, Tettamanti, Iadanza, Fabbro & Perani, 2013;Goral, Naghibolhosseini & Conner, 2013;Bice & Kroll, 2015;White, Malt & Storms, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…This idea has previously been proposed in the literature (for review, see Abutalebi, 2008) based on Green's convergence hypothesis (Green, 2003), which claims that language representations should converge and the neural differences should disappear as proficiency increases. Indeed, our results are coherent with this hypothesis and confirm that L2 proficiency has a major impact on the neural resources needed to manipulate two languages, in accordance with other studies (e.g., Consonni, Cafiero, Marin, Tettamanti, Iadanza, Fabbro & Perani, 2013;Goral, Naghibolhosseini & Conner, 2013;Bice & Kroll, 2015;White, Malt & Storms, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Replication studies showed that effects in the original studies were overestimated (Tajika et al, 2015). Only 36% of replications in psychological research proved to be statistically significant compared to 97% of the original studies (White et al, 2017). White and co-workers (2017) conclude that reproducibility should be one of the core principles of science.…”
Section: Pascal Sienaertmentioning
confidence: 89%
“…Such differences in naming patterns of monolingual vs. bilingual speakers have been observed across a number of languages in many domains, such as color (e.g., Athanasopoulos, 2009;Ervin, 1961;Paramei, D'Orsi, & Menegaz, 2016), household objects (Ameel, Malt, Storms, & Assche, 2009;Malt & Lebkuecher, 2017;Malt, Li, Pavlenko, Zhu, & Ameel, 2015;White, Malt, & Storms, 2017), motion events (Brown & Gullberg, 2011, 2013, emotions (Pavlenko, 2002), and others.…”
Section: Introductionmentioning
confidence: 93%
“…While there are no studies that empirically test all three accounts against each other, Malt and Lebkuecher (2017) attempted to distinguish between conceptual change and lexical coactivation effects in bilingual naming patterns. Earlier studies used a "free naming" task (Ameel et al, 2009;Ameel, Storms, Malt, & Sloman, 2005;Malt et al, 2015;Pavlenko & Malt, 2011;White et al, 2017), where participants must freely come up with a name for each stimulus object. In such situations, it is not clear whether bilinguals are giving a different name from monolinguals due to a change in their underlying conceptual categories in the domain, or due to activation of an alternative word in their lexicon because of crosslinguistic lexical connections.…”
Section: Empirical Comparison Of the Accountsmentioning
confidence: 99%